Improvement of quality of life after renal transplantation in comparison to dialysis: an exploratory study - Lima, Camila; Romão, Maria Aparecida Fadil; Marques, Igor Denizarde Bacelar; Rida , Carmen Mohamad; Yagyu, Elisa Midori; Grassi, Mariana de Freitas (Brazilian Journal of Transplantation, 2011)
Purpose: To assess the quality of life of persons suffering from chronic kidney disease after them having a kidney transplanted. Methods: It was a qualitative research free from explorative character which was conducted by using a tool to assess the quality of life named Medical Outcomes Study 36 item Short from Health Survey (SF36) and variable according to economical classes in 50 patients after kidney trans- plantation; results attained in the analysis when compared to patients under hemodialysis used the same instrument. Statistical analyzes were expressed as median, interquartile range and variations; for comparisons between groups, the Mann-Whiteney was used. Results: Results of SF-36 were expressed as median: functional capacity (FC) 92, physical aspect (PA) 100, pain (P) 74, general healthy aspect (GHA) 63, vitality (V) 70, social aspects (SA) 87, emotional aspects (EA) 100, and mental health (MH) 76. When comparing the presented research to patients under hemodialysis, best rates were found in 6 out of 8 SF-36 compounds: FC, PA, P, GHA, V and MH. SE has remai- ned constant in both groups and SS was lower in transplanted patients. There was statistical significance in FC with p< 0,009. Conclusion: Kidney transplanted recipients had SF-36 scores higher than patients under hemodialysis.